2006
DOI: 10.4049/jimmunol.176.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αIIbβ3 Induces the Adhesion and Activation of Mast Cells through Interaction with Fibrinogen

Abstract: Integrin αIIb, a well-known marker of megakaryocyte-platelet lineage, has been recently recognized on hemopoietic progenitors. We now demonstrate that integrin αIIbβ3 is highly expressed on mouse and human mast cells including mouse bone marrow-derived mast cells, peritoneal mast cells, and human cord blood-derived mast cells, and that its binding to extracellular matrix proteins leads to enhancement of biological functions of mast cells in concert with various stimuli. With exposure to various stimuli, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…The roles played by each of three sCD40L receptors in platelet activation remain to be determined. Moreover, the expression of ␣IIb␤3 is not restricted to platelets and their progenitors as was recently shown with hematopoietic progenitors (64) and mast cells (20), which also expressed ␣5␤1 (65). Like platelets, activated mast cells express both integrins ␣5␤1 and ␣IIb␤3, and CD40L (66), and could be activated via ␣5␤1 and ␣IIb␤3 following their interaction with CD40L.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The roles played by each of three sCD40L receptors in platelet activation remain to be determined. Moreover, the expression of ␣IIb␤3 is not restricted to platelets and their progenitors as was recently shown with hematopoietic progenitors (64) and mast cells (20), which also expressed ␣5␤1 (65). Like platelets, activated mast cells express both integrins ␣5␤1 and ␣IIb␤3, and CD40L (66), and could be activated via ␣5␤1 and ␣IIb␤3 following their interaction with CD40L.…”
Section: Discussionmentioning
confidence: 64%
“…rsCD40L Bound to ␣5␤1-Based on the above results, and because sCD40L also binds to ␣IIb␤3 (10, 11), which is selectively expressed on platelets (18), hematopoietic progenitors (19), and mast cells (20) but not on U937 cells (data not shown), we hypothesized that binding of rsCD40L to U937 cells may also be mediated by other members of the integrin superfamily. We first looked for integrin superfamily members that are expressed on U937, K562, and HEK 293 cells but not on BJAB cells.…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that extracellular matrix proteins (i.e. fibronectin, fibrinogen, and collagen) affect degranulation by mast cells in addition to their adhesion, migration, and inflammatory responses by binding a wide array of integrins expressed by mast cells [44][45][46]. OPN-induced migration by FSMC was virtually blocked by Ab against either CD44 or integrin av (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…BMMCs or fetal liver mast cells (FLMCs) were generated and cultured as described. [25][26][27] BM-derived macrophage (BMM⌽), BM-derived myeloid dendritic cells (BMmDCs), and BM-derived plasmacytoid dendritic cells (BMpDCs) were cultured as described. 14 The following mutant mice were used: DAP10 Ϫ/Ϫ , 20 DAP12 Ϫ/Ϫ , 28 FcR␥ Ϫ/Ϫ , 29 and Syk ϩ/Ϫ .…”
Section: Cellsmentioning
confidence: 99%